2013
DOI: 10.1590/s1982-56762013005000025
|View full text |Cite
|
Sign up to set email alerts
|

Controle biológico da murcha do tomateiro causada por Ralstonia solanacearum e Fusarium oxysporum f. sp. lycopersici por rizobactérias

Abstract: RESUMOA busca por alternativas ao uso intensivo de agrotóxicos no controle de doenças tem recebido grande atenção da pesquisa agrícola. Rizobactérias têm reconhecida capacidade de reduzir doenças em diversas culturas e promover de crescimento de plantas. O objetivo deste trabalho foi avaliar a eficácia de seis isolados de rizobactérias, pré-selecionadas, no controle de Ralstonia solanacearum e Fusarium oxysporum f. sp. lycopersici (FOL), em casa-de-vegetação e relacionar este comportamento a produção de compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Among the intracellular PGPR, the most studied are the rhizobium with leguminous plants symbiosis (Gray and Smith, 2005), and among the extracellular PGPR are the bacteria from the Bacillus and Pseudomonas genera (HarTEMAN et al, 2010;Rocha and Moura, 2013). There are, however, rhizobacteria that can stablish both in the interior and exterior of cells, belonging to both groups, that is, Burkholderia (Gray and Smith, 2005).…”
Section: Rhizobium As Plant Growth Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the intracellular PGPR, the most studied are the rhizobium with leguminous plants symbiosis (Gray and Smith, 2005), and among the extracellular PGPR are the bacteria from the Bacillus and Pseudomonas genera (HarTEMAN et al, 2010;Rocha and Moura, 2013). There are, however, rhizobacteria that can stablish both in the interior and exterior of cells, belonging to both groups, that is, Burkholderia (Gray and Smith, 2005).…”
Section: Rhizobium As Plant Growth Promotersmentioning
confidence: 99%
“…Several species of Bacillus and Pseudomonas are used in biologic control, such as in tomato plants when inoculated with bacteria from these genera, which leads to a reduction of wither symptoms caused by Ralstonia solanacearum and Fusarium oxysporum f. sp. lycopersici (Rocha and Moura, 2013).…”
Section: Indirect Mechanismsmentioning
confidence: 99%
“…Studies on the suppression mechanism of the Bacillus agents indicated that the biocontrol effects of species primarily attribute to their production of various bioactive molecules [9]. Lipopeptide is one of the most important bioactive substances and exhibits excellent properties, such as broad-spectrum antibiotic activity, good stability, low toxicity, high biodegradability, and less prone to drug resistance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the biocontrol mechanisms of Bacillus agents indicated that the biocontrol effects of certain species are primarily associated with their production of various bioactive molecules [9].…”
mentioning
confidence: 99%